2022
DOI: 10.1093/sleep/zsac265
|View full text |Cite
|
Sign up to set email alerts
|

Sleep restriction reduces positive social emotions and desire to connect with others

Abstract: Feeling connected with others and experiencing positive interpersonal interactions is associated with physical health and psychological functioning. Despite the importance of social experiences, experimental studies investigating how sleep impacts social connections and positive social experiences are limited. The current study sought to examine how sleep loss impacted social motivation and emotions. Healthy emerging adults (N=53; 83% female, ages 18-28 years) were randomly assigned to one night of sleep restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“… 34 , 43 Second, from the perspective of reciprocity behavior driven by external factors, the sense of obligation is suggested to drive the participant’s obey the norm of reciprocity due to external factors such as the external pressure of the benefactor’s expectation for repayment and reputation in response to others’ favor. 43 , 58 Consistent with previous studies, 9 there were no significant changes in sense of obligation following sleep loss. Considering that our findings suggest that there is no significant change in benefactor’s expectation of repayment following TSD, this may partly explain why sleep deprivation does not significantly alter the sense of obligation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“… 34 , 43 Second, from the perspective of reciprocity behavior driven by external factors, the sense of obligation is suggested to drive the participant’s obey the norm of reciprocity due to external factors such as the external pressure of the benefactor’s expectation for repayment and reputation in response to others’ favor. 43 , 58 Consistent with previous studies, 9 there were no significant changes in sense of obligation following sleep loss. Considering that our findings suggest that there is no significant change in benefactor’s expectation of repayment following TSD, this may partly explain why sleep deprivation does not significantly alter the sense of obligation.…”
Section: Discussionsupporting
confidence: 83%
“… 4 Total sleep deprivation (TSD) not only affects individual cognitive functions, such as attention, vigilance, and memory, 5 but also raises the risk of physical diseases and mental illnesses. 3 , 6 Recently, emerging research has demonstrated the detrimental impacts of TSD on social functions, 7 such as causing lower empathy, 8 decreased desire to engage in social interactions, reduced gratitude, 9 social withdrawal, 10 decreased helping behavior, 11 increased immoral behaviors, 12 , 13 and decreased trust and cooperation in social dilemmas. 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
“…Diminished positive affect may also serve a more direct protective function when internal sleep pressure is high by reducing an individual’s motivation to seek out social interactions or other pleasurable experiences at a time when cognitive processes and physical capabilities are impaired. Indeed, sleep loss has been shown to result in a desire to maintain more social distance from others (Ben Simon, Vallat, et al, 2020; Palmer, John-Henderson, et al, 2023). It is also possible that the influence of sleep loss on negative affect may be altered based on certain situational characteristics or may only occur for some individuals.…”
Section: Discussionmentioning
confidence: 99%
“…There is a clear association between social interactions and sleep, as indicated by several studies demonstrating that social isolation in older adults is inversely associated with sleep quality and predicts poorer sleep quality in subsequent years [ 45, 46 ]. Study found that restricting sleep duration in adults could diminish their inclination to engage in socialization and reduce positive social emotions [ 47 ]. Similarly, the present study revealed lower engagement in social activities among patients with the difficulty falling asleep type of MCI.…”
Section: Discussionmentioning
confidence: 99%